Employee rights over inventions and innovations in employment in Kenya - Ndungu, Martha Wanjiru (Intellectual Property Research Unit, 2016)
We live in an economy where intangible assets have become valuable commodities. These intangible assets are created by individuals, or groups who apply their creativity and ingenuity appropriately. The result of such ingenuity and creativity is product that is deemed to be so important that it qualifies for legal protection. Such assets will benefit any individual, business, company or enterprise that has the ownership right or title and the ability to commercially exploit the asset. Therefore, there is an interest in the ownership and control of the assets as well as the manner in which legal entitlement is devised by the law. Where, the asset is an invention that is patentable the law has granted the employer ownership. This thesis considers how the law balances the right it gives to the employer and the compensation it grants the inventive employee. The thesis seeks to ensure that an employee-inventor has been adequately compensated for his ingenuity and for producing the fruits of his creativity.